THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL MANAGEMENT SYSTEMS, AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON THE FINANCIAL PERFORMANCE - Saskia Febby Maharantika; Fuad Fuad (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of Environmental Performance Rating (Proper), Environmental Management System (ISO 14001), and Corporate Social Responsibility Disclosure on a company's financial performance. This study is conducted by quantitative methods using secondary data. The purposive sampling method was used to collect data on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for Period 2017-2019, manufacturing companies that participated in the PROPER program during 2017-2019, and manufacturing companies that provided complete data using complete data Rupiah to measure research variables. Panel Regression with Panel Pooled Data was used to analyze the data with statistical application EViews-10. The regression result shows (1) Environmental Performance Rating positively effect and significant on company's financial performance, (2) Environmental Management System certification positively effect and non-significant on company's financial performance, (3) Corporate Social Responsibility Disclosure negatively effect and non-significant on company's financial performance.